2020
DOI: 10.31235/osf.io/g7y69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Donor Financial Capacity Drives Racial Inequality in Medical Crowdsourced Funding

Abstract: In 2018, over 250,000 American families found themselves unable to pay for medical care and turned to the online “crowdfunding” service GoFundMe to raise money online. The $650 million dollars raised from these medical campaigns appear to have filled a sizable hole in the American social safety net. Yet crowdfunding is at heart a network process, and a large body of research shows that social networks can reproduce inequality. In this paper I show that medical crowdfunding indeed replicates patterns of racial,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…Given a relatively small sample size and lack of significance testing for differences between racial groups, we caution against drawing overly strong conclusions about these results. However, these findings do generally align with other research which documents substantial racial disparities in crowdfunding outcomes (Igra, 2021; Kenworthy et al., 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Given a relatively small sample size and lack of significance testing for differences between racial groups, we caution against drawing overly strong conclusions about these results. However, these findings do generally align with other research which documents substantial racial disparities in crowdfunding outcomes (Igra, 2021; Kenworthy et al., 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Despite public support for causes such as hospital and health worker aid, nutrition and PPE, campaigns for individuals and basic needs far outnumbered other purposes. These outcomes lend further credence to observations that crowdfunding is most successful and visible among higher income, better educated and more resourced populations, and less successful among those who need it most (Igra, 2021; Igra et al., 2021; Kenworthy & Igra, 2022; Lukk et al., 2018; van Duynhoven et al., 2019).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The relative success of these campaigns is likely due to a number of factors other than news media coverage. Based on earlier analyses of medical crowdfunding campaign outcomes, these factors include the relative wealth of the crowdfunding campaigner's community and their educational attainments, race, and social connections (Igra, 2021; van Duynhoven et al, 2019). The findings of the current analysis suggest that news media coverage is among these factors of success.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the challenges of collecting robust data from private platforms, only a handful of studies have empirically documented this phenomenon. Studies in both the United States and Canada have found that crowdfunders seek funds to fill common holes in the social safety net, and that campaigns for older people, people of color, and transgender users tend to perform more poorly (Barcelos 2019; Berliner and Kenworthy 2017;Igra 2020;Kenworthy et al 2020;Lukk et al 2018). Duynhoven and colleagues (2019) found that Canadian cancer campaigns were more common in wealthier, better educated, urban areas.…”
Section: Black Boxes and Online Inequitiesmentioning
confidence: 99%